Inhibitory effects and killing kinetics of lactic acid rice gel against pathogenic bacteria causing bovine mastitis - Rinrada Chotigarpa (2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Staphylococcus aureus and S. epidermidis are the major teat skin bacteria and lead to severe bovine mastitis. Teat antiseptic is an important tool for controlling intramammary infection. The antibacterial activity of lactic acid (LA) against one reference strain of S. aureus ATCC 25923 and two field strains including S. aureus and S. epidermidis was investigated using the broth microdilution method. Its minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were 0.5% for strains belonging to both species. An antiseptic preparation containing 5% LA with modified rice gel (LA-RG) was successfully prepared. Rheological behavior of LA-RG was found to be a pseudoplastic flow with thixotropy with viscosity of approximately 0.007 Pas. LA-RG exhibited a sufficient adhesive property in the rolling ball test with a length of 9.67 ± 0.04 cm. Killing kinetic studies of LA-RG showed that the killing rate of LA-RG was significantly faster than that of LA. After 32 min of exposure to LA-RG, approximately 86% and 60% of S. aureus and S. epidermidis were reduced, respectively. Abnormal bacterial cell surface after exposure to LA-RG was observed by scanning electron microscopy. It is concluded that LA-RG is a promising preparation as an alternative product for preventing mastitis in dairy cattle.